Predisposing factors for seroma formation in patients undergoing thyroidectomy: Cross-sectional study. (November 2017) - Ramouz, Ali; Rasihashemi, Seyed Ziaeddin; Daghigh, Faeze; Faraji, Esmaeil; Rouhani, Shahin
Abstract: Introduction: Seroma is defined as collection of fluid within the surgical site during postoperative period that causes several complications. Recognition of predisposing risk factors can lead to avoid seroma formation after thyroidectomy. Materials and methods: A cross-sectional study was carried out during a 3-year period and 678 patients were enrolled the study. We recorded demographic data, past medical history and the type of thyroidectomy were for all patients. We measured total and ionized serum calcium and albumin level in all patients before surgery and a day after it. All patients underwent total or subtotal thyroidectomy and if needed central neck dissection was performed subsequently. Patients underwent serial aspiration If they had seroma formation. Results: The overall post-thyroidectomy seroma incidence was 2.2%. There was no statistically significant correlation while evaluating gender, age and body mass index with post-operative seroma formation. However, seroma formation was significantly higher in patients underwent total thyroidectomy (P = 0.041). The results of postoperative laboratory tests showed a significant lower level of ionized calcium in patients with seroma formation (P < 0.0001). Logistic regression showed statistically significant value for variables including age, BMI and decreased ionized calcium level, in developing of seroma. Conclusion: We showed that Seroma formation was lower during thyroidectomy via electrical vessel sealing system in comparison with previous studies. In our study, older age, greater body mass index and decreased ionized calcium level were predictors of seroma formation.